Effect of hydrolyzed polyacrylamide (HPAM) polymer towards microbiological induced corrosion (MIC) bacteria growth and corrososion rates / Hasrizal Abd Rahman - Abd Rahman, Hasrizal (2021)
Oil and gas production continues to dwindle nowadays, which requires oil and gas operators to deploy various interventions to maintain or increase their production. Hydrocarbon production primarily depends on its natural reservoir pressure. Once reservoir pressure drops, secondary recovery methods are deployed, such as waterflooding or gas flooding. After certain amount of time, production and pressure will drop further and recover more hydrocarbons. Hence tertiary recovery procedures, such as the enhanced oil recovery (EOR) methods have been implemented. In Malaysia, EOR was implemented using the chemical flooding method, which is also known as chemical EOR (CEOR). The two most common chemicals used within this strategy are surfactant and polymer. This study will be focusing on polymer, since according to an internal study by PETRONAS, 90% of the polymer will backflow into the pipeline. Pipelines, which play an important role in transporting hydrocarbons from the offshore platforms to onshore facilities are always exposed to integrity threats, this corrosion acting as the primary threat.